Echo lounge / Nur Iwwani Hairuddin ... [et al.] - Hairuddin, Nur Iwwani; Abdul Aziz, Mohamed Nizam; Mansor Musawir, Nur Aqila Sofea; Muhammad Azman, Hanie Mahirah (2024)
Designing public spaces in educational institutions requires considering sustainability issues, the requirements of students, and sustainable practices. We highlight eco-friendly features by installing environmentally friendly resources that not only reduce environmental impact but also withstand weather conditions like rain, sun, and wind. Timber, also known for its sustainability, serves as the foundation for a retreat-like environment, having a natural aesthetic that encourages relaxation and creativity. Modular design enhances motion, allowing these spaces to adapt to changing needs. Successful public spaces should accommodate a variety of student activities, from studying to socializing, and provide comfortable seating that promotes community and interaction. These environments must resemble the university's environment, promoting a welcoming and functional sense of place. Functionality is essential, ensuring that the design supports a variety of uses while allowing for simplicity of movement and access. By combining aesthetics, sustainability, and modularity, higher education institutions can establish an efficient and environmentally friendly focus for their students, which encourages an environment on campus and the surroundings that facilitates academic as well as social engagement in a variety of scenarios.